Linking diet quality and energy demand in free‐living guanacos: an eco‐physiological innovative approach - Gregorio, Pablo Francisco (2019)
In adaptive terms, animals are subject to challenges imposed by their environment. To address physiological patterns in wild mammals, the non‐invasive study of glucocorticoid hormones has become the main approach through two well‐defined conceptual frameworks: one is related to stress responses, whereas another refers to the glucocorticoids as physiological mediators of the allostatic load, necessary for the maintenance of homeostasis. A key factor to analyse the physiology of wild animals is to understand the relationship between energetic demands and nutritional attributes. The objective of this study was to assess the influence of diet quality on physiological mediators of energy mobilization in two populations of wild guanacos (Lama guanicoe) from Northern Patagonia. In order to evaluate energy mobilization and its relationship with diet quality, we quantified nitrogen content and cortisol metabolite concentrations in fresh faeces. Samples were collected in two contrasting seasons (summer and winter, representing the breeding and non‐breeding seasons respectively). Summer was identified as the period of highest diet quality and energy mobilization, in both sexes and populations. We found quadratic relationships between cortisol levels and nitrogen percentage, which we hypothesize corresponds to two different factors: one of an energetic‐nutritional nature (during winter, the non‐reproductive season), and the other of an energetic‐reproductive nature (during summer, the reproductive season). Our evidence suggests variation in the administration of energy resources in guanacos in response to internal and external stimuli, giving rise to a novel Biphasic Model of energy demand. Our results reinforce the knowledge of the adaptive eco‐physiological attributes of guanaco, and we describe a new conceptual model which explains the energy management patterns for this species and possibly for other ungulates, within the breeding and non‐breeding seasons